Tradução, adaptação e validação da Breastfeeding Self-Efficacy Scale : aplicação em gestantes - Oriá, Mônica Oliveira Batista (2008)
The breastfeeding practice is remarkably important to provide a close contact of the mother-baby dyad and to offer to the newborn a water, energy and protein nutritional source in the early post-natal life. This study had as objectives: translate and adapt the Breastfeeding Self-Efficacy Scale (BSES), apply the Breastfeeding Self-Efficacy Scale- Brazilian version (BSES-BV) to pregnant women, verify the BSES-BV reliability and validity in order to detect women self-efficacy and to verify the association between the BSES-BV scores and the sociodemographic and obstetric variables. In this regard, a copy-right authorization was obtained to use the BSES, which underwent a transcultural adaptation process as indicated by Beaton (1998), and submitted to psycometric analyses (reliability and validity). In order to do this, a methodological study was developed using a quantitative approach held at a Health Center in Fortaleza. The sampling includes 117 pregnant women whom were interviewed before or after the prenatal appointement. The data collection was done during July to October, 2007, using not only the BSES-BV but also a field form to gather sociodemographic and obstetric information. Following the adaptation, a 33 item-scale was achieved, in which, misunderstanding issues resulted in the insertion of examples within 12 itens. A committee of experts evaluated the BSES-BV content and found a Content Validation Index of 0.86 to the scale and a Cronbach alpha of 0.88, pointing out to high internal consistency, corroborated by the intra-class correlation coefficient ranging from 0.83 to 0.90. The scale stabillity was evaluated by the Spearman-Brown coefficient, which was shown to be high (0.80 and 0.91) indicating high stability of the BSES-BV. The construct validity evaluated by the factorial analysis, undergoing major component analysis with varimax rotation, suggested the withdrawal of some items; however, we decided to keep them to furture instrument use in a more representative sampling of this population and others that exhibit characteristics yet not addressed. The construct validity by means of contrasted group comparisons suggests that only the experience might not be relevant to reach women’s breastfeeding self-efficacy, hence breastfeeding experience must be previously satisfactory and gratifying in order to reach a greater self-efficacy during the later breastfeeding behavior. In conclusion, we have obtained a reliable and valid instrument, enabling the evaluation of the women’s self-efficacy perception regarding the breastfeeding practice and herein we recommend that the BSES-BV should be applied to either research or to the obstetric practice, since it allows the identification of factors related to breastfeeding that deserves appropriate and effective attention from the breastfeeding professionals.